PROGRAM CSR DALAM PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH DENGAN KOMPOSTER - Aramia Fahriyah; Delfiana Matasik; Irwan Irwansyah; Ssudarwanto; Anita Maulina (Indonesian Community Service and Empowerment Journal (IComSE), 2026)
ABSTRACT   Corporate Social Responsibility (CSR) is a company’s commitment to supporting sustainable development through integrated efforts in the social, economic, and environmental sectors. In Indonesia, CSR has been legally regulated and is mandatory for certain companies, particularly those operating in natural resource–based industries, through the Limited Liability Company Law and Government Regulation No. 47 of 2012 as the main legal framework. CSR programs are designed based on the needs of communities surrounding the company’s operational areas, with the aim of creating sustainable positive impacts through an empowerment-based approach. One implementation of CSR is carried out in Harapan Jaya Sub-district, Bekasi City, by PT Bridgestone Tire Indonesia in collaboration with Institut STIAMI, focusing on household waste management. This community empowerment activity is divided into several stages. First, program planning and socialization. Second, joint program formulation with the community. Third, training on waste management using composters. Fourth, development of composter outputs through greening training. Fifth, to strengthen understanding and provide a real environmental perspective, a comparative study visit was conducted to a location that has successfully implemented waste management in Sunter Sub-district, Jakarta. Sixth, the launching of the Kampung Komposter program and a Fashion Show Competition themed Creative Waste Recycling. The results of this activity indicate that CSR, particularly community empowerment programs themed around waste management using composters implemented by PT Bridgestone Tire Indonesia, directly contributes to the community through environmental improvement. Environmental benefits are reflected in the reduction of waste generation in RW 16, Harapan Jaya Sub-district, Bekasi City, resulting in a cleaner and healthier environment. Meanwhile, other empowerment benefits are seen in economic value, as composter outputs in the form of solid compost and liquid processed products (Liquid Organic Fertilizer) contribute to community empowerment through economic improvement.